Tren urbanisasi pada secondary cities di Indonesia periode tahun 1990-2010 - Katherina, Luh Kitty (Jurnal Kependudukan Indonesia, 2014)
Urbanization is identical to the main city in the country as a location of the capital accumulation that is the main attraction of high economic activities. But in fact, the phenomenon of urbanization has penetrated even mega-urbanization in the second tier cities in the country. This paper takes the case of Indonesia’s secondary cities that are beginning to have an important role in moving the national economy and balancing regional development. The cities are Surabaya, Bandung, Medan, Semarangand Makassar. These cities are experiencing accelerated growth in demography, economic and physical. These growth spurt cause land requirements in cities are no longer able to be fulfilled so the urban activities began to spread to the surrounding areas. Urban areas is widening to suburban areas. National Population Censuses in the period 1990-2010 shows the rate of population growth in the secondary cities lower than their surrounding areas. This indicates that urban activities of secondary cities had passed the administrative boundaries of the city, merge with the surrounding area. This paper will describe the trends of urbanization that occurred in Indonesia’s secondary cities using descriptive analytic approach through comparison of data from National Population Censuses 1990, 2000 and 2010. In general, the trends of urbanization in Indonesia’s secondary cities shows a pattern that is the rate of population growth in urban area closely related to the size of the city.